Long-Term Treatment Outcomes of Primary Alveolar Bone Grafts for Alveolar Clefts: A Qualitative Systematic Review. (January 2022) - Carbullido, M. Kristine; Dean, Riley A.; Kamel, George N.; Davis, Greta L.; Hornacek, Michael; Segal, Rachel M.; Ewing, Emily; Lance, Samuel H.; Gosman, Amanda A.
Background: Alveolar bone grafting is utilized to manage alveolar clefts in patients with cleft lip and palate. However, the timing of bone grafting is variable with conflicting evidence supporting the use of primary alveolar bone grafting (PABG) in clinical practice. Primary Aim: To provide a qualitative systematic review analysis of long-term outcomes after PABG. Materials and Methods: A qualitative systematic review was performed following the Cochrane Handbook and reported using Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Summative findings were evaluated using Confidence in the Evidence from Reviews of Qualitative research to assess the quality of evidence supporting the findings. Results: After removing duplication, 2182 publications were identified, and 2131 were excluded after screening through titles and abstracts. Inclusion criteria for this study included patients who underwent PABG at 24 months of age or younger and a minimum of 5 year follow-up. Thirty-two publications met the inclusion criteria and were included for qualitative analysis. Primary outcome measures included cephalometric analysis, bone graft survival, occlusal analysis, hypomineralization, tooth eruption, radiograph analysis, and arch relationships. Four assessment themes were characterized from the systematic review: (1) bone graft survival, (2) craniofacial skeletal relationships, (3) occlusion and arch forms, and (4) recommendations for utilizing PABG in practice. Conclusion: The reported systematic review provides evidence that performing PABG leads to poor long-term outcomes related to bone graft survival and maxillary growth restriction despite some reported positive outcomes.